2022
DOI: 10.1101/2022.06.02.494602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility of 3T layer-dependent fMRI with GE-BOLD using NORDIC and phase regression

Abstract: Introduction: Functional MRI with spatial resolution in the submillimeter domain enables measurements of activation across cortical layers in humans. This is valuable as different types of cortical computations, e.g., feedforward versus feedback related activity, take place in different cortical layers. Layer-dependent fMRI (L-fMRI) studies have almost exclusively employed 7T scanners to overcome the reduced signal stability associated with small voxels. However, such systems are relatively rare and only a sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…One example is the hippocampus, which is located right above the air-filled ear canals. While there are specific neuroscientific hypotheses with predictions of memory encoding and memory retrieval across the layers in hippocampus, previous layer-fMRI studies of the hippocampus at 7T have been extremely difficult (Chang et al 2022;Deshpande et al 2022;Koster et al 2018;Maass et al 2014;Zhang et al 2022). Due to the reduced susceptibility artifacts at 3T, we believe that developments shown in this study will help facilitate more straightforward applications of layer-fMRI in susceptibility-challenged brain areas.…”
Section: Layer-fmri Vaso At 3t Enables Additional Studies That Cannot...mentioning
confidence: 84%
See 3 more Smart Citations
“…One example is the hippocampus, which is located right above the air-filled ear canals. While there are specific neuroscientific hypotheses with predictions of memory encoding and memory retrieval across the layers in hippocampus, previous layer-fMRI studies of the hippocampus at 7T have been extremely difficult (Chang et al 2022;Deshpande et al 2022;Koster et al 2018;Maass et al 2014;Zhang et al 2022). Due to the reduced susceptibility artifacts at 3T, we believe that developments shown in this study will help facilitate more straightforward applications of layer-fMRI in susceptibility-challenged brain areas.…”
Section: Layer-fmri Vaso At 3t Enables Additional Studies That Cannot...mentioning
confidence: 84%
“…Previous layer-fMRI studies have been conducted at 3T (Akin and Özen 2019; Kim and Ress 2017; Knudsen et al 2022; Koopmans et al 2010; Lifshits et al 2018; Markuerki-aga et al 2020; Olman et al 2007; Puckett et al 2016; Ress et al 2007; Scheeringa et al 2016; Taso et al 2021; Wu et al 2018). Those studies were somewhat limited by unwanted sensitivities of large draining veins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One very promising denoising candidate is NOise Reduction with DIstribution Corrected (NORDIC) PCA (49). This approach of NORDIC-PCA denoising for layer-fMRI at 3T has been advocated for BOLD fMRI protocols by Knudsen et al (6). First investigations of ongoing research indicated that this approach is similarly helpful for layer-fMRI VASO.…”
Section: Denoising Toolsmentioning
confidence: 99%